(untitled) (The Research of Medical Science Review, 2024)
Multiple factors mediate and mitigate the link between Adverse Childhood effect (ACE) and drug abuse. We investigated whether the associations between ACE and co-use, nicotine usage, and cannabis use are mediated by stress, and whether the effects of this mediation changed depending on emotional interest. In addition to answering questions about demographics, ACE, stress, and drug misuse, 249 participants finished a delay discounting assignment. The snowball sampling method was applied. Hayes' PROCESS macro (V3.4, Model 15) was used to analyze the data using moderated mediation and Pearson correlations. The findings indicate that ACE and drug misuse are related, and that stress acts as a mediator in this relationship. The variable of emotional interest moderates the relationship between ACE and stress.